2008
DOI: 10.1111/j.1541-4337.2007.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Modeling to Enhance the Microbiological Safety of the Food System

Abstract: This article is part of a collection entitled "Models for Safety, Quality, and Competitiveness of the Food Processing Sector," published in Comprehensive Reviews in Food Science and Food Safety. It has been peer-reviewed and was written as a follow-up of a pre-IFT workshop, partially funded by the USDA NRI grant 2005-35503-16208.ABSTRACT: The use of modeling techniques for safety and risk prediction in the food supply is strongly supported by the incidence of foodborne outbreaks worldwide. In microbiological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 67 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…Tailing has been attributed to the presence of a few large clumps of cells or a more heattolerant subspecies of cells (19,25,35). To account for deviations from first order kinetics, researchers have obtained D-values from the linear portion of the curve (2,21,52) or have used mathematical models to address nonlinearity (5,12,22,23). Although mathematical models are helpful for predicting the death rate of microbial populations, they have limitations when determining thermal death parameters (26).…”
Section: Resultsmentioning
confidence: 99%
“…Tailing has been attributed to the presence of a few large clumps of cells or a more heattolerant subspecies of cells (19,25,35). To account for deviations from first order kinetics, researchers have obtained D-values from the linear portion of the curve (2,21,52) or have used mathematical models to address nonlinearity (5,12,22,23). Although mathematical models are helpful for predicting the death rate of microbial populations, they have limitations when determining thermal death parameters (26).…”
Section: Resultsmentioning
confidence: 99%
“…Since pressure-treated foods first appeared on the market, significant advances in the modeling of microbial inactivation have been accomplished (e.g., McMeekin et al 1993;Baranyi and Roberts 1995;Peleg and Cole 1998;Xiong et al 1999a;Ahn et al 2007b;Corradini and Peleg 2007;Klotz et al 2007;Koseki and Yamamoto 2007b;Black and Davidson 2008;Pérez Lamela and Torres 2008b). Many authors have reported that in thermal processes, the survival curves for microorganisms deviate from the expected linear behavior (Kamau et al 1990;Bhaduri et al 1991;Linton et al 1995Linton et al , 1996Anderson et al 1996;Buzrul 2007).…”
Section: Nonlinear Microbial Inactivation Kinetics Modelsmentioning
confidence: 98%
“…The effects of such variability can be included using the COMSOL Multiphysics interface directly, as already mentioned under property estimation. Finally, there are a number of risk factors associated with microbiological food safety which have not been modeled to date and that could contribute to the overall safety of a food product (Black and Davidson, 2008).…”
Section: Limitations Of the Predictive Softwarementioning
confidence: 99%